ANALISIS FINANCIAL MANAGEMENT BEHAVIOR ANAK MUDA PENGGEMAR BUDAYA KOREA DI INDONESIA - Dyah Ayu Putri Cahyaningtyas (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Indonesia is a potential market for the South Korean economy. The interest of the Indonesian people in Korean culture is substantial and young people are fans of Korean culture. Especially in Korean music, young people are not afraid to spend a lot of money to meet their needs. However, it was later discovered that the financial condition of young people in Indonesia is classified as unhealthy because many young people still do not understand how to manage finances properly. Therefore, the researcher wants to test whether financial socialization, financial experience, financial self-efficacy and locus of control affect the financial management behavior of young Korean culture fans in Indonesia. This research focuses on young people aged 18-30 years who are members of a fan club for Korean music fans. The sample used consisted of 368 samples and the sampling method used was non-probability sampling. The sampling design used purposive sampling. Research data were obtained through questionnaires distributed online. The data analysis technique uses Multiple Linear Regression and the SPSS 25 software test tool. In this research, the results reveal that financial socialization, financial experience, financial self-efficacy, and locus of control have an effect. It has become an essential role in the financial management behavior of young fans of Korean culture in Indonesia. So young Indonesians expect to improve and pay attention to these four factors in order to have the ability to manage finances and good financial conditions in the future.